Information Literacy Skills of First-Year Library and Information Science Graduate Students: An Exploratory Study - Hebert, Andrea (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2018)
Objective – This cross-sectional, descriptive study seeks to address a gap in knowledge of both information literacy (IL) self-efficacy and IL skills of students entering Louisiana State University’s Master of Library and Information Science (MLIS) program.Methods – An online survey testing both IL self-efficacy and skills was administered through Qualtrics. The online survey instrument used items from existing instruments (Beile, 2007; Michalak & Rysavy, 2016) and was distributed to two cohorts of incoming students; the first cohort entered the MLIS program in fall 2017, and the second entered in spring 2018.Results – Data varied between cohorts and between survey instruments for both IL self-efficacy and skills; however, bivariate analysis of data indicated a moderate positive correlation between overall IL self-efficacy and demonstrated IL skill scores in both fall 2017 and spring 2018 cohorts.Conclusion – The study indicates a need for a larger, multi-institutional study using a rigorously validated instrument to gather data and make generalizable inferences about the IL self-efficacy and skills of incoming LIS graduate students.